Giants Within: A Tale of Two Rare Abdominal Behemoths - Kanishka Konar; Anup Kumar; Utpal De (National Board of Examinations Journal of Medical Sciences)
Hidden deep within the abdomen, giants can grow in silence—unseen, unfelt, and often undetected until they command attention with mass effect or incidental discovery. We present two such formidable entities: a rare giant adrenal angiomyolipoma and an enormous retroperitoneal liposarcoma—each a pathological paradox, pushing anatomical boundaries and clinical expectations. Their sheer size, silent progression, and rarity challenge diagnostic acumen and surgical dexterity alike. These cases are not mere enlargements of common pathologies; they are singular narratives of stealth, size, and surgical spectacle. Through them, we explore the thin line between benign and malignant, routine and extraordinary in retroperitoneal tumours.